Tổng hợp và cấu trúc một số hợp chất loại azometin imit từ 5-phenylpyrazolidin-3-on - Tuyết Lan, Hoàng Thị; Kiều Oanh, Đoàn Thị; Đĩnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2015)
A series of nine azomethine imides has been synthesized by condensation of 5-phenylpyrazolidin-3-on with aromatic aldehydes. The structure of reported compounds has been confirmed by IR, MS, 1H NMR and NOESY spectra. A proton chemical shift sign for distinction of the azomethine imide and the azomethine groups was proposed.